Effectiveness of Service Training Based on Education and Training Model On-In-On-In for Dual Skills Program - Purnomo, Purnomo; Wahyudi, Dian Julianto; Yoto, Yoto; Dika, Johan Wayan (BRILIANT: Jurnal Riset dan Konseptual, 2021)
The focus in this article is to reveal: (1) The purpose of participating in dual skills programs; (2) Effectiveness of In Service Training 1 (In-1); (3) Effectiveness of In Service Training 2 (In-2); (4) Competence Pedagogic and Dual Professional Teacher Skills. Dual Skills Program is the addition of assignments and functions of teachers from normative and adaptive teachers plus the task of teaching productive expertise competencies, carried out for 12 months using the On-In-On-In learning model. Type of case study research with multi-case study design. The results of this study (1) Motivation of teachers to participate in dual skills programs to obtain educator certificates and anticipate shortages of hours; (2) Implementation of In-Service Training 1 is quite effective; (3) Implementation of In Service Training 2 (In-2) is quite effective;Â  (4) In general On-In-On-In training is quite effective; (5) Teacher competency after training is quite good. Constraints that occur are difficult to divide the teaching time and tasks from training dual skills programs which are quite a lot. To the development of science, especially vocational education, the results of this study are expected to be used as one of the comparative studies on the theory of the effectiveness of On-In-On-In training in obtaining dual related skills: (a) The purpose of participating in a dual expertise program (b) Effectiveness of In Service Training 1 (In-1), (c) Effectiveness of In Service Training 2 (In-2), (d) Competence of Dual Skills Teachers Post-On-In-On-In Training.